The teachers’ readiness to incorporate Information and Communication Technology (ICT) in the teaching and learning of English as a Second Language in Zimbabwe’s Urban Primary Schools - Sylod none Chimhenga (Journal of Research in Social Science and Humanities, 2025)
Any nation's ability to educate its citizens depends on its teachers, thus teacher preparation is essential to the integration of ICT in teaching. The success of ICT integration in the classroom therefore depends on the teachers' readiness to incorporate these tools into the curriculum. No paradigm shift in the educational process can be successfully imagined without teachers being the first participants of the intention. This study set out to find out how urban primary school English teachers in Zimbabwe felt about their own preparedness to use ICTs in the classroom. The resources that are available, the abilities of the teachers, our urban primary schools in the Bulawayo Metropolitan Province were the target population. Qualitative research methodology was employed in the study. Data were gathered for this study using ten randomly chosen English teachers from 3 selected primary schools of Bulawayo. The teachers' preparedness was investigated using semi-structured interviews. The results demonstrated that English teachers lacked the necessary preparation to both integrate ICT into the teaching and learning process and execute blended learning. Teachers view ICT in blended learning positively, however the existing ICT tools were insufficient for teaching and learning since there was little to no technical support available to assist teachers who needed it.  The study provided several recommendations, including that teachers should receive ongoing training, be aware of the value of ICT, and ensure that schools have working ICT resources that are available to them.